2014
DOI: 10.1039/c3cy00705g
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on surface reactivity of Nb-doped vanadyl pyrophosphate catalysts by reactivity experiments and in situ Raman spectroscopy

Abstract: The effect of Nb when used as a promoter for vanadyl pyrophosphate, the catalyst for the oxidation of n-butane to maleic anhydride, was investigated. By means of both reactivity experiments and in situ Raman spectroscopy, it was found that the promoting effect shown by Nb occurred already for a very low amount of it, i.e., for a V/Nb atomic ratio as high as 150. The main role of Nb was to accelerate the formation of a limited amount of δ-VOPO 4 on the surface of vanadyl pyrophosphate, by prompting the oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Different states of Vi ons can be evidenced; both V 5 + (binding energy (BE): 517.1 eV)a nd V 4 + (BE: 516.1 eV) ions can be detected on the WV sample, whereas ah igherV 5 + /V 4 + surfacer atio is shown for the extra-framework Vs pecies in the ion-exchanged sample, VO-WO x .C onsidering that the ion exchange was performed by using vanadyl ions (VO 2 + ), the XPS results point out ap artial oxidation process during catalystp reparation, consistently more severe in the case of the extra-framework Vs pecies. Moreover,t he VPP catalystp resentsV 4 + as the predominant species, but the presence of V 5 + is also significant, despite the fact that the XRD pattern only shows the presence of (VO) 2 P 2 O 7 ;t his observation agrees with previousr eports by other authors, [35][36][37] who attribute the presence of V 5 + speciest ot he coexistence of VOPO 4 domains in additiont o( VO) 2 P 2 O 7 on the surface of the catalyst. Finally,t he VCoAPO sample shows both V 5 + /V 4 + ions, whereas V 5 + is mainly observed on the VO x /VCoAPOs ample.…”
Section: Resultssupporting
confidence: 89%
“…Different states of Vi ons can be evidenced; both V 5 + (binding energy (BE): 517.1 eV)a nd V 4 + (BE: 516.1 eV) ions can be detected on the WV sample, whereas ah igherV 5 + /V 4 + surfacer atio is shown for the extra-framework Vs pecies in the ion-exchanged sample, VO-WO x .C onsidering that the ion exchange was performed by using vanadyl ions (VO 2 + ), the XPS results point out ap artial oxidation process during catalystp reparation, consistently more severe in the case of the extra-framework Vs pecies. Moreover,t he VPP catalystp resentsV 4 + as the predominant species, but the presence of V 5 + is also significant, despite the fact that the XRD pattern only shows the presence of (VO) 2 P 2 O 7 ;t his observation agrees with previousr eports by other authors, [35][36][37] who attribute the presence of V 5 + speciest ot he coexistence of VOPO 4 domains in additiont o( VO) 2 P 2 O 7 on the surface of the catalyst. Finally,t he VCoAPO sample shows both V 5 + /V 4 + ions, whereas V 5 + is mainly observed on the VO x /VCoAPOs ample.…”
Section: Resultssupporting
confidence: 89%
“…30,35 On the other hand, surface-sensitive characterization via HRTEM and in situ XPS suggest that an amorphous layer on the catalyst surface is responsible for catalytic activity via formation of isolated VO x sites segregated from the bulk VPO material. 31,34,36,37 The VPO catalyst is synthesized via reaction of V 2 O 5 and H 3 PO 4 in either aqueous or organic media. This reaction leads to the formation of VOHPO 4 •0.5H 2 O, which is then heated to eliminate water, either in situ in the butane oxidation reactor or in a dedicated synthesis reactor.…”
Section: Mixed Metal Oxidesmentioning
confidence: 99%
“…31,40 Other studies found that dopants such as Nb led to weaker binding of maleic anhydride on the surface, decreasing the rate of overoxidation. 9,37 More detailed discussion on the VPO catalyst will be presented in section 5.4.3 of this review.…”
Section: Mixed Metal Oxidesmentioning
confidence: 99%
“…There are many patents and papers describing catalysts that convert acetic acid and formaldehyde into acrylic acid. The main catalyst system known to affect this transformation, a vanadium phosphorus oxide (VPO) catalyst, is also known for its ability to oxidize butane to maleic anhydride and for its use in some condensation reactions. , Eastman Chemical Company has described a V, Ti, P mixed oxide catalyst and then modified the catalyst with alkali metal . BASF SE has invented a catalyst that includes VPO as an active ingredient, carrier and accelerator.…”
Section: Introductionmentioning
confidence: 99%
“…These doped VPO catalysts proved beneficial due to changes in their redox properties, particle size and catalytic performances. Caldarelli et al discussed the effect of Nb when used as a promoter for VPO catalysts in the oxidation of n -butane to maleic anhydride. Through the ex situ and operando / in situ experiments, it was shown that Nb plays two important roles.…”
Section: Introductionmentioning
confidence: 99%